"Undoing" (or Symbolic Reversal) at Homicide Crime Scenes1. Issue 2 (9th June 2017) - Russell, Maria; Schlesinger, Louis B.; Leon, Maria; Holdren, Samantha
Abstract: A closed case file review of a nonrandom national sample of 975 homicides disclosed 11 cases (1.13%) of undoing, wherein offenders engaged in crime scene behavior that has been considered an attempt to symbolically reverse the murder. The frequency of the various methods of undoing involved the use of blankets to cover the victim's body (55%), positioning the body (55%), use of a bed or couch (42%), washing the body (36%), using pillows (36%), as well as removing clothing and adding other types of adornments (27%). Ten of the 11 offenders were male, and one was female; all 12 victims were female. Ten of the 12 victims were family members or relationship intimates. These findings are consistent with prior reports which concluded that the motivation for undoing behavior is an attempt to compensate for guilt or remorse for having committed the homicide.